Distribution of Lg coda Q in Xinjiang and its adjacent regions - 徐彦 毛燕 胡家富 苏有锦 丛连理 (Acta seismologica sinica, 2005)
In this study, we collected 1 156 broadband vertical components records at 22 digital seismic stations in Xinjiang region, Ueruemqi station, and 7 stations in the adjacent regions during the period of 1999-2003. The records were firstly processed by the stacked spectral ratio method to obtain Q sub(0) (Q at 1 Hz) and the frequency correlation factor corresponding to each path. Based on the results, the distribution images of Q sub(0) and in 11 grids for Xinjiang region were gained by the back-projection technique. The results indicate that Q sub(0) is high (300-450) in the Tarim platform and marginal Siberian platform, while Q sub(0) is low (150-250) in the southern regions as west Kunlun fold system and Songpan-Ganzi fold system. In the northern regions as Junggar fold system and Tianshan fold system, Q sub(0) is also low (250-300) and varies between 0.5 and 0.9.